Anisotropic Magnetoresistance Effect of Nickel Nanowires - Pham, Do Chung; Ngo, Van Thanh; Wegrowe, Jean-Eric (Communications in Physics, 2021)
In this work, we study the magnetic properties of nickel nanowires by measuring their anisotropic magnetoresistance at room temperature. The single nickel nanowire is grown by electrodeposition in a polymer membrane (Polycarbonate). We measure the anisotropic magnetoresistance effect of nickel nanowires for the various values of the magnitudes and orientations of an external magnetic field. The results clearly show the existence the anisotropic magnetoresistance effect in the nickel nanowires. Besides, the experimental data are best fit to the analytical calculations using the Stoner-Wohlfarth model for the magnetization of the wires.